Pengaruh Perilaku Herding, Risk Aversion terhadap Keputusan Investasi dengan Financial Attitude Sebagai Variabel Moderating - Iwan Santoso; Hermanto Liu (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study was to identify the relationship between herding behavior, risk aversion on investment decisions with financial attitude as a moderating variable. To obtain the data, the researcher used a questionnaire that utilized the purposive sampling method in obtaining respondents who were appropriate and in line with this research. Total found 110 respondents. This research finds that herding behavior has a negative effect on investment decisions, risk aversion has a significant positive effect on investment decisions. Financial attitude can be a moderating variable for herding and risk aversion in investment decisions.